PENGARUH BELANJA LANGSUNG DAN SISA LEBIH PERHITUNGAN ANGGARAN (SiLPA) TERHADAP PERTUMBUHAN EKONOMI (Survei Pada Pemerintah Daerah Kabupaten/Kota di Provinsi Sulawesi Tengah) - Novandy, Andrie (Katalogis, 2015)
This research’s aims are: 1) to define and analyze the influence of direct expenditure and budget surplus on economic growth; 2) to define and analyze the influence of direct expenditure on economic growth; 3) to define and analyze the influence of budget surplus on economic growth. The research involves ten regencies and one city that are purposively selected. The research type is descriptive analysis with quantitative approach. The data is analyzed with multiple linear regressions. Based on the study results, the research concludes that: 1) direct expenditure and budget surplus simultaneously ave positiveand significant influence on economic growth with Rsquare of 0.2840 or 28,4 % on the significant influence on economic growth with tvalue of 2,797 on the significant level of 0,008; 3) budget surplus partially has insignificant influence on economic growth with tvalue of 0,927 on the significant level of 0,359.